2013
DOI: 10.1186/1477-7819-11-212
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of preoperative serum alpha-fetoprotein (AFP) level and prognosis of hepatocellular carcinoma (HCC) after hepatectomy

Abstract: BackgroundTo investigate the prediction value of preoperative serum alpha-fetoprotein (AFP) level for the prognosis of hepatocellular carcinoma (HCC), by comparing pathological characteristics, recurrence rate and survival rate after hepatectomy.Methods108 cases of HCC patients who received liver resection in our hospital from 2005 to 2011 were enrolled in this study. According to preoperative serum AFP level, the patients were divided into AFP ≤ 20 ng/mL group, AFP 20 to 400 ng/mL group and AFP > 400 ng/mL gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 17 publications
7
98
2
Order By: Relevance
“…Elevation of ALT usually indicates liver cell damage, while total TBil and ALB are clinical indices reflecting the extent of liver injury and liver function decompensation. AFP is a glycoprotein most commonly found in HCC patients and also exists in serum in pregnancy, active liver disease, and embryonic gonad tumors (26). We excluded pregnancy, HCC, and embryonic gonad tumors, so AFP was related to active hepatic injury in our enrolled subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Elevation of ALT usually indicates liver cell damage, while total TBil and ALB are clinical indices reflecting the extent of liver injury and liver function decompensation. AFP is a glycoprotein most commonly found in HCC patients and also exists in serum in pregnancy, active liver disease, and embryonic gonad tumors (26). We excluded pregnancy, HCC, and embryonic gonad tumors, so AFP was related to active hepatic injury in our enrolled subjects.…”
Section: Resultsmentioning
confidence: 99%
“…In a large Chinese retrospective cohort, high serum AFP level correlated with larger HCC size, vascular invasion and low tumor differentiation [57] . Previous studies showed that AFP levels could be useful to predict recurrence after surgery [58,59] , liver transplantation [60][61][62] . The value of AFP as a prognostic marker was reported in several studies evaluating sorafenib in advanced HCC.…”
Section: Poorer Prognosismentioning
confidence: 99%
“…Poorly differentiated tumor, large tumor size, macrovascular invasion and microvascular invasion are independent predictors of poor survival and tumor recurrence after hepatectomy and transplantation (Jun et al 2012;Ma et al 2013;Marelli et al 2008;Pawlik et al 2005;Rodriguez-Peralvarez et al 2013;Wayne et al 2002;Xu et al 2014;Zhao et al 2012). Pre-operative assessment of the differentiation grade could help in predicting prognosis, allowing appropriate patient selection for liver resection or transplant allocation.…”
Section: Introductionmentioning
confidence: 96%